Multi−scale computational modelling in biology and physiology - Southern, J; Pitt−Francis, J; Whiteley, J; Stokeley, D; Kobashi, H; Nobes, R; Kadooka, Y; Gavaghan, D (2015)
Recent advances in biotechnology and the availability of ever more powerful computers have led to the formulation of increasingly complex models at all levels of biology. One of the main aims of systems biology is to couple these together to produce integrated models across multiple spatial scales and physical processes. In this review, we formulate a d